2011
DOI: 10.1111/j.1538-7836.2011.04235.x
|View full text |Cite
|
Sign up to set email alerts
|

EMMPRIN (CD147/basigin) mediates platelet–monocyte interactions in vivo and augments monocyte recruitment to the vascular wall

Abstract: Summary. Background: Platelets play a central role in hemostasis, in inflammatory diseases such as atherosclerosis, and during thrombus formation following vascular injury. Thereby, platelets interact intensively with monocytes and enhance their recruitment to the vascular wall. Objectives: To investigate the role of the extracellular matrix metalloproteinase inducer (EMMPRIN) in platelet-monocyte interactions. Methods and Results: Isolated human monocytes were perfused in vitro over firmly adherent platelets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 64 publications
0
55
0
1
Order By: Relevance
“…33,34 In this context, it is interesting to note that the extracellular matrix metalloproteinase inducer (EMMPRIN) was recently identified as a leukocyte counterreceptor for GPVI expressed by neutrophils. 35,36 When addressing the extent of endothelial damage during the early phase of the rpA reaction, we observed that the endothelial lining was generally preserved but displayed alterations in regions of neutrophil infiltration, thus suggesting that endothelial injury and/or endothelial retraction contribute to inflammatory bleeding. Surprisingly, whether in GPVI 2/2 or thrombocytopenic mice, not all vessels supporting neutrophil infiltration bled.…”
Section: Discussionmentioning
confidence: 96%
“…33,34 In this context, it is interesting to note that the extracellular matrix metalloproteinase inducer (EMMPRIN) was recently identified as a leukocyte counterreceptor for GPVI expressed by neutrophils. 35,36 When addressing the extent of endothelial damage during the early phase of the rpA reaction, we observed that the endothelial lining was generally preserved but displayed alterations in regions of neutrophil infiltration, thus suggesting that endothelial injury and/or endothelial retraction contribute to inflammatory bleeding. Surprisingly, whether in GPVI 2/2 or thrombocytopenic mice, not all vessels supporting neutrophil infiltration bled.…”
Section: Discussionmentioning
confidence: 96%
“…The observed effects of OxLDL on platelet-monocyte interactions were dependent on the concentration and the degree of oxidative modification of LDL. Although platelet-monocyte interactions involve a variety of receptor-counter-receptor pairs, such as CD147/basigin or CD11b/CD18-glycoprotein Ib α (GPIbα), 29,30 and are also modulated by secreted soluble mediators, such as CXC motif ligand 16 (CXCL16) or CX3-C motif ligand 1 (CX3CL1), 31,32 our findings reinforce P-selectin as the key initial mediator for platelet-leukocyte interactions because blocking P-selectin-PSGL-1 interactions virtually abrogated platelet interaction with monocytes. P-selectin has previously been shown to be involved in the development and exacerbation of atherosclerotic lesions by bridging platelets to leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…70 Signaling through PSGL-1 rapidly upregulates leukocyte expression of aMb2 71 that binds platelet GPIba 72 or GPIIbIIIa via a fibrinogen intermediate ( Figure 3B). 73 The complexes are further stabilized by multiple receptor-ligand interactions including CD40-CD40 ligand, 74 extracellular matrix metalloproteinase inducer-glycoprotein VI (GPVI), 75 lymphocyte function-associated antigen 1-ICAM-2, 76 and junctional adhesion molecule-C-aMb2. 77 PSGL-1 engagement can also activate cooperative signaling through NF-kB to induce the production of proinflammatory cytokines.…”
Section: 65mentioning
confidence: 99%